2008
DOI: 10.3171/ped/2008/2/9/194
|View full text |Cite
|
Sign up to set email alerts
|

The Dandy–Walker variant: a case series of 24 pediatric patients and evaluation of associated anomalies, incidence of hydrocephalus, and developmental outcomes

Abstract: Object The Dandy–Walker complex is a continuum of aberrant development of the posterior fossa that has been associated with multiple congenital anomalies, radiographic abnormalities, and developmental delay. The Dandy–Walker variant (DWV) is a unique entity believed to represent a milder form of the complex, and is characterized by a specific constellation of radiographic findings. In this retrospective case series, the authors report the association of the DWV with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 36 publications
2
60
1
8
Order By: Relevance
“…Studies have shown that behaviors of the autistic spectrum may also be found in conditions involving the Dandy-Walker complex (9) . In spite of the controversial findings in the literature, alterations in the cerebellum present in the Dandy-Walker variant have been described in cases that present manifestations of the autistic spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that behaviors of the autistic spectrum may also be found in conditions involving the Dandy-Walker complex (9) . In spite of the controversial findings in the literature, alterations in the cerebellum present in the Dandy-Walker variant have been described in cases that present manifestations of the autistic spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…The literature points out various possibilities of alterations in development in individuals who present conditions of Dandy-Walker complex (9) . As the Dandy-Walker variant is the mildest form of the complex, the occurrence of asymptomatic conditions is possible, this being dependent on the etiologic factor of these malformations or of the presence of associations with other clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 of 24 patients (41.7%) have either patent ductus arteriosus, ventricular septal defect, atrial septal defect, transposition, hypoplastic right heart, or pulmonary artery stenosis. 10 …”
Section: Introductionmentioning
confidence: 99%